Islet Allotransplantation in the Bone Marrow of Patients With Type 1 Diabetes: A Pilot Randomized Trial. Issue 4 (April 2019) - Maffi, Paola; Nano, Rita; Monti, Paolo; Melzi, Raffaella; Sordi, Valeria; Mercalli, Alessia; Pellegrini, Silvia; Ponzoni, Maurilio; Peccatori, Jacopo; Messina, Carlo; Nocco, Angela; Cardillo, Massimo; et al.
Abstract : Background: Results in murine and nonhuman primate suggested that the bone marrow (BM) might be an alternative site for pancreatic islet transplantation. Methods: We report the results of 2 clinical studies in patients with type 1 diabetes receiving an intra-BM allogeneic islet transplantation: a feasibility study in patients with hepatic contraindications for liver islet allotransplantation receiving a single intra-BM islet infusion (n = 4) and a pilot randomized trial (1:1 allocation using blocks of size 6) in which patients were randomized to receive islets into either the liver (n = 6) or BM (n = 3) to evaluate islet transplant function and survival. Results: We observed no adverse events related to the intrabone injection procedure or the presence of islets in the BM. None of the recipient of an intra-BM allogeneic islet transplantation had a primary nonfunction, as shown by measurable posttransplantation C-peptide levels and histopathological evidence of insulin-producing cells or molecular markers of endocrine tissue in BM biopsy samples collected during follow-up. All patients receiving islets in the BM except 1 lost islet function during the first 4 months after infusion (2 with an early graft loss). Based on biopsies and immunomonitoring, we concluded that the islet loss was primarily caused by the recurrence of autoimmunity. Conclusions: Bone marrow is not a suitable alternative site for pancreatic islet allotransplantation in patients with type 1 diabetes. Abstract : Supplemental Digital Content is available in the text.